Menumbuhkan Hobi Dan Bakat Anak-Anak Panti Asuhan Pembangun Didikan Islam Untuk Meningkatkan Keterampilan Hidup - Ade Rafiah Addini Awaliyah; Fajar Utama Ritonga (Pengelola Jurnal Politeknik Negeri Ketapang, 2023)
Life skills are various skills or abilities to be able to behave positively and adapt to the environment that enables a person to face various demands and challenges in his daily life effectively. One that includes life skills for adolescents is vocational skills, the point of which is how to turn hobbies and talents into independent living businesses. Hobby is a recreational activity that is done in spare time to calm one's mind. Talent is an innate ability in the form of potential that still needs to be developed or trained to achieve specific skills, knowledge and skills. Hobbies and talents are very useful for growing potential within. The author has carried out practicum activities at the Islamic Education Builders Orphanage which is guided and supervised by Mr. Fajar Utama Ritonga, S.Sos, M.Kesos as the school Supervisor and also the Teaching Lecturer for Practicum II Courses. The author chose 14 clients to carry out a mini project, namely